Sources concerned with the history of local government in Yekaterinoslav Province in 1870 - 1914 - Vadym Korobka (Cхід, 2013)
The set of sources concerned with the history of local government inYekaterinoslavProvinceof the late 19th- the early 20th century is composed of publications and materials available in the archives. Considerable part of those sources is kept in the national archives ofDnepropetrovsk,Donetsk, Zaporizhia and Lugansk Districts as well as in the Russian State Historical Archives. All the sources are divided into the following groups: 1) legal acts, 2) paper management, 3) statistics, 4) periodicals and 5) descriptions. The high representative level of the sources, their profoundness and faithfulness make it possible to get quite a clear idea of local government inYekaterinoslavProvince, its arrangement and practices in the aforementioned period.